An analysis of sugar production trends in Ukraine and an analytical forecast of its development - Панасенко, Наталія Леонідівна (Technology audit and production reserves, 2015)
Sugar production is one of the most important branches of the agro-industrial complex in Ukraine. At the moment, the situation in the sugar market is unstable. To a significant extant, this is due to poor efficiency of control of the sector. Scientifically-based forecasting of production trends is an important methodology for raising administrative effectiveness. The objective of this work is the analysis of changes in trends in the performance of sugar production in Ukraine and the improvement of the technical approach to the forecasting of sugar production in the regions, and the leaders in the sugar production sector. Since 2012, in all the sugar producing regions of Ukraine, there has been a decline in sugar production and sugar beet growing. The main factor for the reduction in sugar production is the excess of its supply over demand due to a trend of reduced need in the population. Further expansion of production, notwithstanding the reduced demand in the domestic market, is possible through sugar export growing. It requires: increasing of product quality, bringing it in to line with European standards, and providing domestic sugar competitiveness in the export market. Further development of sugar production in Ukraine requires State support to the sugar production sector. Scientifically-based forecasting of the production indicators is essential for the development of State and Regional support programmes. Sugar production trend in Poltava region, one of the sector leaders in Ukraine, has been researched. A conclusion has been drawn on the efficiency of the exponential forecasting to assess the total future production.